Regional differences in nitrogen balance and nitrogen use efficiency in the rice–livestock system of Uruguay - Castillo, Jesús; Kirk, Guy J. D.; Rivero, M. Jordana; Haefele, Stephan M. (Frontiers in Sustainable Food Systems, 2023)
The reconnection of crops with livestock systems is proposed as a way of sustainably intensifying food production globally with reduced environmental impacts, particularly those involving nitrogen (N). Detailed understanding of processes governing N fluxes and budgets is needed to design productive and efficient systems. The aim of this study was to investigate regional differences in N balance (NBAL, defined as all N inputs minus outputs), use efficiency (NUE, defined as N outputs / inputs × 100) and surplus (NSURP, defined as all N inputs minus only outputs in food products) in the rice-livestock system of Uruguay over the last 18 years. Three regions across Uruguay are distinguished based on soil fertility and length of pasture rotation. The northern region has high soil fertility and shorth length of rotation (HFSR); the central region has medium soil fertility and medium length of rotation (MFMR); the eastern region has low fertility and long pasture rotation (LFLR). Results show a very high NUE (90%) for the rice component in all rotations, associated with negative NBALs ranging from -35 kg N ha-1 yr-1 in HFSR to -3 kg N ha-1 yr-1 in LFLR. However, the livestock component, which overall had a low productivity in animal food products (< 2 kg N ha-1 yr-1), had low NUE (< 10%) but positive NBALs in all the rotations, sustaining N supply in the rice component. At the system level, NUE was high (60%) and NBAL was slightly positive in all rotations (from + 2.8 kg N ha-1 yr-1 in HFSR to +8.5 kg N ha-1 yr-1 in LFLR). Because of a recent increase in the fertilizer N dose in rice, NSURP was intermediate (40 kg N ha-1 yr-1) and should be monitored in the future. Even with the very good N parameters values attained, there is an opportunity to improve the system efficiency by improving the livestock component.